Ability of Melon (Cucumis melo. L) Fruit Juices Based Tris Diluent on The Quality of Frozen Spermatozoa of Bali Cattle After Thawing - Mujahidurrohman Mujahidurrohman; Enny Yuliani; Lukman HY (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The high potassium content in melon plays a role in maintaining the normal function of the muscles, heart, nervous system, and potassium is also the main regulator of blood pressure. The aim of this study was to evaluate the effect of using melon juice (Cucumis melo L.) as a diluent on the quality of spermatozoa and semen of Bali cattle both before and after freezing. The Banyumulek Artificial Insemination Center produces sperm used in Bali cattle breeding. The technique used was a completely randomized design (CRD) with 4 treatments and 15 replications. The first treatment was 100% egg yolk tris buffer without the addition of melon juice (P0), the second treatment was 80% buffer without the addition of 20% melon juice (P1), the third treatment was 60% buffer with the addition of 40% melon juice (P2). The fourth treatment was 40% buffer with the addition of 60% melon juice (P3). The outcomes showed that the worth of flawless plasma film and mortality upsides of ox-like semen after weakening and subsequent to defrosting were not essentially unique. Be that as it may, not altogether disparate in that frame of mind of motility, level of reasonability, level of ordinariness and post-defrosting anomalies. According to the findings of this study, melon juice can be used as an alternative extender for fresh Bali cattle sperm and preserve the quality of spermatozoa.